Placement and sizing of thyristor controlled series compensator using PSO based technique for loss minimization - Jumaat, S.A.; Musirin, I.; Othman, M.M.; Mokhlis, Hazlie (2012)
Minimizing the transmission loss in power system is one of the important issues in power system research these days. Transmission loss can be reduced by installing reactive power compensation components. Installing the thyristor controlled series compensator (TCSC) in power system has been known to increase the voltage level in the system and hence reduce the system losses. This paper describes placement and sizing of FACTS devices based on Particle Swarm Optimization for minimization of transmission loss considering voltage profile and cost function. Particle Swarm Optimization (PSO) is one of the artificial intelligent search approaches which have the potential in solving such a problem. In this study one of FACTS device is used as a scheme for transmission loss. For this study, TCSC is chosen as the compensation device. Validation through the implementation on the IEEE 30-bus system indicated that PSO is feasible to achieve the task. The simulation results are compared with those obtained from the Evolutionary Programming (EP) technique in the attempt to highlight its merit.